Analisis Historis Teologi Terhadap Peran Gmit Galed Kelapa Lima Bagi Moralitas Sosial Di Kelurahan Kelapa Lima: Analisis Historis Teologis - Janter Rano Baki; Maria R. A. Pada; Yuda D. Hawu Haba; Endang Damaris Koli (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
Since its formation, the GMIT Galed Kelapa Lima Congregation has still faced problems of social morality in Kelapa Lima Village, Kupang City. The problem of morality has not diminished, but has become more prevalent nowadays due to the existence of traditional massage service places and bars at the Sasando Hotel and Citra Hotel around Galed residents, thus providing onsite and online access for covert prostitution services. This article aims to explore past tensions that have an impact on the present, by exploring the role of GMIT Galed Kelapa Lima in historical and contemporary contexts. This article uses a qualitative method with a Church History approach. Data collection techniques used, namely field research and literature review. The results of the research show that all this time the Galed church has focused on internal consolidation and set aside these issues. Therefore, I offer a holistic service model to answer the problem of social morality, namely: First, the importance of sex education in the family, educational institutions and the church. Second, develop the Galed ministry which focuses on Transformative Diakonia. Third, service management approach through SWOT analysis. Fourth, the Galed Church is partnering with the Kupang City Government to develop a shared vision for preventing covert prostitution.